Gambaran status gizi dan siklus menstruasi pada remaja putri - Rehuellah Daniella Karambut; Maureen Irinne Punuh; Ester Candrawati Musa (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Nutritional status plays an important role in maintaining reproductive health among adolescent girls. Both undernutrition and overnutrition may disrupt the balance of reproductive hormones, including estrogen, progesterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH), potentially leading to menstrual cycle irregularities. Purpose: To describe the nutritional status and menstrual characteristics of adolescent girls attending all junior high schools. Method: A descriptive study with a quantitative approach was conducted among adolescent girls enrolled in six junior high schools in Manganitu District. Total sampling was employed. A total of 161 participants were included in the nutritional status analysis, while menstrual characteristics were analyzed among 132 participants who had experienced menarche. Nutritional status was assessed through anthropometric measurements of weight and height and classified using the Body Mass Index-for-Age (BMI-for-Age) according to WHO standards. Menstrual characteristics were collected using a structured questionnaire through face-to-face interviews. Data were analyzed descriptively using frequencies, percentages, means, and standard deviations. Results: The mean age of the participants was 13.17 ± 0.81 years (range: 12–16 years). Most participants had normal nutritional status (78.8%), while 10.5% were obese, 6.2% were overweight, and 4.5% were undernourished. Among the 132 participants who had experienced menarche, 68.2% had a normal menstrual cycle (21–35 days), whereas 31.8% had an abnormal menstrual cycle. Furthermore, 72.7% of participants reported experiencing dysmenorrhea, and 81.8% reported mood changes during menstruation. Conclusion: Most adolescent girls had normal nutritional status and a normal menstrual cycle. However, undernutrition, overweight, obesity, and abnormal menstrual cycles were still observed in a considerable proportion of participants. These findings highlight the importance of continuous nutritional monitoring and reproductive health education to promote the health and well-being of adolescent girls. Keywords: Adolescent Girls; Junior High School; Menstrual Cycle; Nutritional Status; Reproductive Health.